Exposure to Androstenes Influences Processing of Emotional Words - d'Ettorre, Patrizia; Bueno, Steve; Rödel, Heiko G.; Megherbi, Hakima; Seigneuric, Alix; Schaal, Benoist; Roberts, S. Craig (Frontiers in Ecology and Evolution, 2018)
There is evidence that human-produced androstenes affect attitudinal, emotional and physiological states in a context-dependent manner, suggesting that they could be involved in modulating social interactions. For instance, androstadienone appears to increase attention specifically to emotional information. Most of the previous work focused on one or two androstenes. Here, we tested whether androstenes affect linguistic processing, using three different androstene compounds. Participants (90 women and 77 men) performed a lexical decision task after being exposed to an androstene or to a control treatment (all compounds were applied on the philtrum). We tested effects on three categories of target words, varying in emotional valence: positive, competitive, and neutral words (e.g., hope, war, and century, respectively). Results show that response times were modulated by androstene treatment and by emotional valence of words. Androstenone, but not androstadienone and androstenol, significantly slowed down the reaction time to words with competitive valence. Moreover, men exposed to androstenol showed a significantly reduced error rate, although men tended to make more errors than women in general. This suggests that these androstenes modulate the processing of emotional words, namely some particular lexical emotional content may become more salient under the effect of androstenes.